2016
DOI: 10.1186/s12967-016-1085-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long noncoding RNA expression in hepatocellular carcinoma of different viral etiology

Abstract: BackgroundDysregulation of long noncoding RNA (lncRNA) expression contributes to the pathogenesis of many human diseases, including liver diseases. Several lncRNAs have been reported to play a role in the development of hepatocellular carcinoma (HCC). However, most studies have analyzed lncRNAs only in hepatitis B virus (HBV)-related HCC or in a single group of HCC patients regardless of the viral etiology.MethodsTo investigate whether lncRNAs are differentially expressed in HCC of different viral etiology, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 51 publications
1
54
0
Order By: Relevance
“…Because HULC can influence lipid biosynthesis in liver, we probed the level of HULC during HCV infection. The results were found to be in the expected line with earlier reports including patient samples (Hammerle, Gutschner, et al, ; Zhang et al, ; Zhang et al, ). So we further investigated the relevance of HULC in hepatitis C virus life cycle and its ensued pathogenesis.…”
Section: Introductionsupporting
confidence: 91%
“…Because HULC can influence lipid biosynthesis in liver, we probed the level of HULC during HCV infection. The results were found to be in the expected line with earlier reports including patient samples (Hammerle, Gutschner, et al, ; Zhang et al, ; Zhang et al, ). So we further investigated the relevance of HULC in hepatitis C virus life cycle and its ensued pathogenesis.…”
Section: Introductionsupporting
confidence: 91%
“…Although many attributes of LncRNAs, such as patterns of expression, remain largely unknown, LncRNAs have been shown to play important roles in transcriptional, posttranscriptional, translational and epigenetic gene regulation [9,10]. An increasing amount of evidence has revealed that different LncRNAs might be associated with HCC [11]. With regard to these latter effects, previous molecular-based studies found that certain LncRNAs promote tumor initiation, cancer cell growth, and metastasis during the development of HCC [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The development of effective treatment is critical for ischemia stroke, because it causes high mortality and disability worldwide. LncRNAs are a newly discovered class of regulators in the cerebral vascular endothelium after ischemic injury, such as stroke [29]. In recent years, non-coding RNAs have emerged as novel targets to treat ischemia stroke [30,31].…”
Section: Discussionmentioning
confidence: 99%